Peranan Qawaid Al-Fiqhiyyah dalam Pencatatan Perkawinan - Noor Izzati Amelia; Vichi Novalia; M. Riyas Rasyid; Lisnawati Lisnawati (STIKes Ibnu Sina Ajibarang, 2025)
Qawaid al-Fiqhiyyah are fundamental principles in Islamic law that serve as guidelines for establishing legal rulings, including in the context of marriage registration. Although, in Islam, the validity of a marriage is determined by the fulfillment of its pillars and conditions, marriage registration becomes crucial in state law to ensure legal certainty and provide protection for married couples and their children. The application of fiqh principles such as